A function availability-based integrated product-service network model for high-end manufacturing equipment. (December 2018) - Chang, Fengtian; Zhou, Guanghui; Xiao, Xiaoping; Tian, Changle; Zhang, Chao
Highlights: A function availability-based integrated product-service network model is proposed. The networked modeling method is applied to solve the integration and mapping problems. The function goals, structure objects and service processes are the integrated elements. The function network, structure network, service network and network of networks are built. The model realizes the integration of products and MRO services for high-end manufacturing equipment. Abstract: Nowadays, product-service system (PSS) has become a popular topic that devotes to implement the integration of products and services to meet function demands. However, in the usage phase, the integration of high-end manufacturing equipment (HEME) and maintenance-repair-overhaul (MRO) services is still insufficient to ensure the long-term continuous availability for function implementation (named as function availability). Thus, in view of function information in function availability, this paper develops a function availability-based integrated product-service network model (IPSN) from the perspective of complex network. This model merges the obtained function action units, structure module units as well as service execution activities and reveals their implement-maintain-ensure mapping mechanism based on the modeling processes of function network, structure network, service network and interdependent network of networks. In this model, functions are regarded as the goals serviced, structures are deemed as the objects serviced and services are the corresponding execution processes. With this model, the function availability could be better ensured with the delivery of the linked more critical integrated services. In order to illustrate the detailed modeling process, a case for feeding function of numerical control honing machine 2MK2263 × 200 is studied. From the evaluation and comparison results, it could be seen that this model not only realizes the integration of products and services to ensure the concerned functions, but also provides a vital foundation for the identification of critical nodes and the effective service configuration for availability.